1999
DOI: 10.1029/98je02820
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of olivine by H+ and He+ bombardment

Abstract: Abstract. Laboratory simulations of solar wind irradiation of olivine, a constituent of ordinary chondritic meteorites and S-type asteroids, show a dramatic chemical reduction of surface iron and, to a lesser extent, silicon. Earth's atmosphere oxidizes any reduced iron instantaneously, whereas irradiated material on the surface of an asteroid would remain reduced. Changes in optical reflectance, due to metallization of the surface, provide a possible explanation for differences in the near-infrared spectra of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
97
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 48 publications
14
97
0
1
Order By: Relevance
“…This result finds support by earlier experiments (Wang et al 1998;Wang & Ewing 1992;Dukes et al 1999). Apparently, such chemical changes are very sensitive to the energy range, as the experiments by Demyk et al (2001) and Bradley (1994) show, who found chemical effects by their experiments with ions of an energy range between 4 and 10 keV.…”
Section: Conclusion Of Astrophysical Relevancesupporting
confidence: 80%
See 2 more Smart Citations
“…This result finds support by earlier experiments (Wang et al 1998;Wang & Ewing 1992;Dukes et al 1999). Apparently, such chemical changes are very sensitive to the energy range, as the experiments by Demyk et al (2001) and Bradley (1994) show, who found chemical effects by their experiments with ions of an energy range between 4 and 10 keV.…”
Section: Conclusion Of Astrophysical Relevancesupporting
confidence: 80%
“…Apparently, such chemical changes are very sensitive to the energy range, as the experiments by Demyk et al (2001) and Bradley (1994) show, who found chemical effects by their experiments with ions of an energy range between 4 and 10 keV. The process of selective sputtering is strongly depending on the energy of the ions but, probably, also on the experimental conditions (Dukes et al 1999). A compositional processing of enstatite by interaction of interstellar cosmic rays should only occur at very low energies.…”
Section: Conclusion Of Astrophysical Relevancementioning
confidence: 83%
See 1 more Smart Citation
“…Recently Dukes et al (1999) performed KeV range proton and helium bombardment on olivine surface. The total particle doses in their experiments are from 10 16 to 10 18 cm −2 , somewhat larger than that of our experiments.…”
Section: Dependence On Proton Implantationmentioning
confidence: 99%
“…Irradiation causes chemical changes in the irradiated region of silicates [Dukes et al, 1999;Daviosne et al, 2008] as well as enhances the reactivity of the surface [Lanford and Burman, 1983;Cantando et al, 2008] including the potential to form OH bonds [Gruen et al, 1976] and increases diffusivity [Dienes and Damask, 1958]. Samples returned during the Apollo era have been in storage for over 40 years, and even though they have been stored in a nitrogen purged atmosphere, trace amounts of water vapor and hydrogen could diffuse into the materials.…”
Section: Astrophysical Motivationmentioning
confidence: 99%